The Correlation between Literature, History and Culturein the Select Novels of Olga NawojaTokarczuk:A Cultural Materialist Reading - Prasad Pandey, Sanjay; Jacob, Paul (International Journal of Psychosocial Rehabilitation, 2021)
Olga Tokarczuk’s novels combine the elements of an ordinary culture, an epic of Polish history, and very factual mythology of daily life. Literature, history, and culture are the inseparable elements, according to the cultural materialists. The paper is an attempt to identify the "residual," "emergent," and "oppositional" cultural elements in the select novels of Olga Tokarczuk. It attempts to diagnose the hidden political agenda and power structures in the novels of Olga Tokarczuk and simultaneously look for potential subversive aspects to relate the texts to the present, i.e., the inseparability of the linguistic and the social in the structure of discourse. The study involves using the past to’read’ the present, revealing the politics of a society by what it chooses to emphasize or suppress the past.